The Buddhist Philosophy of Universal Flux: An Exposition of Philosophy of Critical Realism as Expounded by the School of Dignaga - Kizhakkekara, Sebastian (Journal of Dharma, 1984)
Satkari Mookeriee The Buddhist Philosophy of Universal Flux (An Exposition of Philosophy of Critical Realism as Expounded by the School of Dignaga) Delhi: Motilal Banarsidass, 1980, pp. xvii +448, Rs. 100/-